Does COVID-19 Cause Hemorrhagic Encephalitis? A Case Report - Marzieh Abutorabi Zarchi; Roghayeh Razavi; Nasim Namiranian (Case Reports in Clinical Practice)
SARS-CoV-2 causes an inflammatory disease characterized by symptoms such as fever, cough, shortness of breath, and myalgia, along with leukopenia, lymphopenia, elevated serum aspartate aminotransferase levels, and abnormal chest computed tomography findings. It may also lead to respiratory distress, unilateral complications, and secondary infections. COVID-19 infection can result in severe neurological complications, including viral encephalitis, cerebrovascular disorders, acute diffuse encephalomyelitis, and acute necrotizing encephalopathy. Here, we report a case of hemorrhagic encephalitis due to SARS-CoV-2 in a 27-year-old patient with a history of type 1 diabetes.